Resilience and hopelessness mediate the relationship between benevolent childhood experiences and life satisfaction: evidence from a cross-cultural study - Melih Sever; Oktay Tatlıcıoğlu; Telma Catarina Almeida; E. P. Abdul Azeez; Sónia Caridade; Olga Cunha (BMC Psychology)
Abstract Background A growing body of literature focuses on the role of benevolent childhood experiences (BCEs) in predicting adulthood well-being, in addition to adverse childhood experiences (ACEs). However, cross-cultural differences are generally ignored in this endeavor. Hence, this study aimed to explore the role of BCEs in predicting life satisfaction, resilience, and hopelessness. We also examined the potential of resilience and the role of hopelessness in mediating the relationship between BCE and life satisfaction. Methods A total of 850 university students from Turkey (n = 371), Portugal (n = 248), and India (n = 231), aged 17 to 58 years (M = 22.12, SD = 4.41), participated in the study. Participants completed an online protocol consisting of measures to assess BCEs, life satisfaction, resilience, and hopelessness. Results BCEs, hopelessness, and life satisfaction have significantly differed among the samples based on the country of residence. BCEs were positively correlated to resilience and life satisfaction and negatively to hopelessness. In the sequential mediation model, after controlling for country and sex, resilience and hopelessness sequentially mediated the relationship between BCEs and life satisfaction. BCEs were associated with life satisfaction, resilience, and hopelessness across countries and sexes. The model explains 42.8% of the variability. Conclusion Despite differences between countries, BCEs are important predictors of adult well-being in all three countries and should be monitored along with ACE. Further, resilience seems to have an important role in lowering the negative consequences of lower BCEs and feelings of hopelessness, pointing to the need to strengthen psychological resilience among adults.